Evaluation des perturbations biologiques chez les brûlés admis aux urgences [Evaluation of biological disorders in burn patients admitted on emergency unit ] - Ibtissem Kihel; Mourad Nachi; Fouzia Berrahal; Yousra Meguenni; Zineb Tahiri (Journal de la Faculté de Médecine d'Oran)
Objective- Burns damage the skin and tissues, and depending on the burn’s degree and the burn surface area of the body, can lead to organ failure causing several biological disturbances. The present study's objective is to evaluate biological disturbances in a cohort of adult and child burns admitted to the emergency Department of the specialized burn hospital in Oran (Algeria). Materials & Methods- This is a retrospective study extending from October 2023 to April 2024.The clinical data analyzed are age, gender, and surface area of the burned body (ABB). The biological variables taken into consideration are blood sugar, albumin, transaminases , CRP, blood ionogram, and blood count.The data were analyzed with SPSS version 20 software. Results- 539 patients were included in our study with 213 (40%) adults aged 18 to 92 years and 326 (60%) children aged 12 months to 17 years. Our results revealed that the main biological abnormalities observed respectively in adults and children are as follows: hyperglycemia (47%, 55%) hypoalbuminemia (22%, 27%), the elevation of AST transaminases (47%, 4%), ALT (45%, 88%), hyponatremia (32%, 38%), hyperkalemia (3%, 18%), hypokalemia (23%, 22%), CRP (33%of children), hyperleukocytosis (71%, 73%), Anemia (18%, 38%) and thrombocytosis (38%, 71%). A significant correlation was found in the adult series between the surface area of the burned body greater than 10% and hyperleukocytosis. Conclusion- Biological assessment upon admission to the emergency room is necessary to detect damages and guide treatment. The study of predictive biomarkers is also important to be able to predict the prognosis of the burn in order to optimize the management of burn patients.